The Effect of Health Education on Postpartum Mothers' Knowledge About Exclusive Breastfeeding At The Ongkaw Health Center, Sinonsayang District - Kumajas, Jean Debora; Tamunu, Esther N.; Lombogia, Moudy; Pasambo, Yourisna; Tololiu, Tinneke (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2023)
Background: In Indonesia, postpartum mothers often find wrong habits in breastfeeding their babies, namely feeling that their milk production is not enough to fulfill their baby's nutrition and giving early complementary foods to their babies. Objective: This study was to determine the effect of health education on postpartum mothers' knowledge about exclusive breastfeeding at the Ongkaw Health Center, Sinonsayang District. Methods: This type of research is a preexperimental design with one group pre-post test conducted on 42 respondents determined by purposive sampling. Data collection was obtained from the results of filling out a knowledge questionnaire, analyzed using the Wilcoxon Signed Rank Test. Results: the study showed that the pre-test knowledge was less knowledgeable with an average value of 23.00. then in the post test the knowledge was good with an average value of 39.00. Conclusion: from the research, namely knowledge in respondents there is a significant effect (p value 0.000; α0.05), which means that there is an effect of health education on the knowledge of postpartum women about exclusive breastfeeding. Suggestions are expected to add insight into the community as information and increase knowledge about exclusive breastfeeding in breastfeeding for babies.